Electron Microscopical Study of Spermatozoa of the Cestode Dilepis undula (Cyclophyllidea, Dilepididae) - Swiderski, Z.; Salamatin, R.V.; Tkach, V.V. (Вестник зоологии, 2000)
The fine structure of spermatozoon of the dilepidid cestode Dilepis undula is described. The main structural elements of the sperm cell are: 1) plasma membrane and underlying single row of cortical microtubules; 2) a single axoneme of the unique platyhelminth 9+˝1˝ type; 3) periaxonemal sheath composed of the crystalline-like material; 4) elongated electron-dense nucleus; 5) crested body. The similarities and differences between the ultrastructure of spermatozoa of D. undula and that of some other cestodes, are briefly discussed.